Assistance for Black Garlic UMKM Actors Pondok Berkah Medan in Analyzing Antioxidant Content - Widawati, Widawati; Afrinis, Nur; Arapani, Laura; Trihendarini, Any (Global Sustainability Research Institute, 2025)
Pondok Berkah Medan, a partner in this community service activity, is an MSME actor producing black garlic with sales reaching more than 100 monthly units. This community service aim is to improve the understanding of MSME actors publishing product claims, namely antioxidant content on product packaging and advertisements following laws and regulations. The method used in this community service activity is active participation in discussions with MSME actors. Community service activities consist of: 1) Identification of MSME’s actor needs, 2) Analysis of antioxidants (flavonoids and antioxidant activity), 3) Education and practice of including product claims on product packaging and advertisements, and 4) Evaluation. The results of this community service show that MSME actors can understand how to include product claims on black garlic product packaging and advertisements following laws and regulations. MSME actor has black garlic products with product claims of antioxidant content. This activity is expected to help MSME actor claim their product correctly.